Cost Minimization Analysis of a Running Firm with Economic Policy - Mohajan, Haradhan Kumar (Annals of Spiru Haret University. Economic Series, 2022)
In this paper the Cobb-Douglas production function is operated in a firm for the analysis of the cost minimization policies. In an economic world, gain of profit depends on the efficient use of raw materials and use of various techniques of the cost minimization. A firm’s main target is to make maximum profit. Scientific based and efficient but minimum cost procedures will favor in this regard. To increase local and global demands, a firm of course develop production sector. An attempt has been taken in this study to minimize cost by considering four inputs, such as capital, labor, raw material, and other inputs to form the economic model subject to a production constraint within the budget.